Point of Sale Terminal Services and the Performance of Small and Medium-sized Enterprises in Nigeria. - Ogunsuyi, Olalekan; Tejumade, Siyanbola Omowumi (International Journal of Social and Management Studies, 2021)
The adoption of Point of Sale (POS) Terminal by Small and Medium-sized Enterprises (SMEs) is expected to ease their means of financial transaction and improve their general performance. However, whether this has been achieved is yet to be discussed. The study therefore investigates the influence of POS terminal services on the performance of the SMEs in Lagos state, Nigeria. Employing a survey research design, the study population comprised of 69,865 registered merchants in Nigeria. 400 questionnaires were administered using a Taro Yamane formula. The data gathering tools were structured questionnaires designed by the researcher to gather data from the respondents on the influence of the POS terminal service on the performance of their businesses. Frequency distribution, percentages, and regression analysis were used for data analysis. The result indicates that POS terminal services has helped increase the sales volume, reduces queues for payment, and increase the income of the business owners.